Completeness of Informed Consent Documentation in the Medical Records of Surgical Patients at Hospital X Kendari - Fatma Kurniasih; Juminten Saimin; Waode Sitti Asfiah Udu (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
Background: An informed consent form is essential to ensure that a patient comprehends all the provided information before making a decision and giving consent. It is crucial for patients to understand the proposed medical actions thoroughly. Completing informed consent forms is vital as they serve as legal documentation to protect patients from any medical procedures and ensure healthcare protection in case of unforeseen harmful events. Purpose(s): This research aims to assess the completeness of informed consent forms in the medical records of surgical patients at Hospital X Kendari in 2024. Methods: This research is an observational descriptive study with a cross-sectional approach. It was conducted at Hospital X Kendari, utilizing 92 samples of informed consent forms for surgical procedures in 2023. Data collection was carried out using checklist sheets. Results: The results showed that the completion of informed consent forms was 90% complete for the identity identification component, 85% for the important report component, 99% for the declaration of consent to action component, and 97% for the authentication component. Conclusion: The analysis of the overall completeness of informed consent foms for surgical patients in 2023 showed a completion rate of 93%.